2014
DOI: 10.12954/pi.14054
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and diagnostic performance of the prostate-specific antigen level with the diagnosis, aggressiveness, and bone metastasis of prostate cancer in clinical practice

Abstract: PurposeThe common tool for diagnosing prostate cancer is serum prostate-specific antigen (PSA) testing and digital rectal examination, but the disadvantage of the high sensitivity and low specificity of PSA testing in the diagnosis of prostate cancer is a problem in clinical practice. We studied the correlation and diagnostic performance of the PSA level with cancer diagnosis, aggressiveness of prostate cancer (Gleason score>7), and bone metastasis.MethodsA total 1,116 patients who underwent transrectal ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 30 publications
7
40
0
6
Order By: Relevance
“…It showed a positive correlation with the number of bone metastatic lesions and increased following bone metastasis upstaging. It is also important for malignant tumor curative effect evaluation, clinical stage, and prognosis (Lojanapiwat et al, 2014;Fizazi et al, 2015). This study result showed that serum BSP, ALP, ICTP, and PSA levels were elevated in prostate cancer patients and were higher in the bone metastasis group compared with nonbone metastasis group.…”
Section: Discussionmentioning
confidence: 75%
“…It showed a positive correlation with the number of bone metastatic lesions and increased following bone metastasis upstaging. It is also important for malignant tumor curative effect evaluation, clinical stage, and prognosis (Lojanapiwat et al, 2014;Fizazi et al, 2015). This study result showed that serum BSP, ALP, ICTP, and PSA levels were elevated in prostate cancer patients and were higher in the bone metastasis group compared with nonbone metastasis group.…”
Section: Discussionmentioning
confidence: 75%
“…4 Salah satu parameter dalam mendeteksi adanya pembesaran prostat adalah pemeriksaan kadar ProstateSpecific-Antigen (PSA) dalam darah. 5,6 Prostate-Specific-Antigen merupakan suatu protein yang disekresikan oleh kelenjar prostat. Jumlah sekresi PSA ditentukan oleh banyak faktor seperti adanya proses inflamasi, pembesaran baik BPH dan keganasan, serta manipulasi kelenjar prostat pada pemeriksaan colok dubur, masase prostat, ataupun pemasangan kateter.…”
Section: Pendahuluanunclassified
“…Beberapa penelitian mengemukakan bahwa korelasi antara kadar PSA dengan volume prostat dapat menentukan adanya progresivitas terhadap pembesaran prostat. 5,6,9 Ras dan etnis diteliti memiliki pengaruh terhadap pembesaran prostat. 2,10,11 Terdapat perbedaan jaringan kelenjar prostat antara ras Asia dengan ras kulit putih di Negara Barat seperti Eropa dan Amerika.…”
Section: Pendahuluanunclassified
“…In a study of 1116 it had been proved that the chance of detecting bone metastasis was greater when the srum PSA level was >20 ng/ml by Lojanapiwat et al [13]. In a study of 48 patients of Ca.…”
Section: Discussionmentioning
confidence: 96%